Guideline for Development Elder Persons Potentiality in Community Development Participation in Khon Kaen Province - Weerasin, Witoon; Siramongkolkan, Thanakorn; Suphan, Promchai; Sittivongsa, Boonpeng (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2020)
The objectives of the research article were 1) to study the potential of the elderly to participate in community development in Khon Kaen Province 2) to analyze the factors affecting the development of the potential of the elderly in the development of the community in Khon Kaen province and 3) to study the potential development guidelines Elderly in community development in Khon Kaen Province. The samples groups 50 persons. The research tool was a questionnaire. The statistics that were used for data analysis were Frequency, Percentage, Mean and Standard Deviation. The research result were found that: 1. Potential level of the elderly to participate in community development in Khon Kaen Province the following are arranged in descending order psychological, physical, intellectual, social relations and community development respectively. 2. Factors Affecting the Potential of Elderly Development in Community Development in Khon Kaen Province Regarding factors affecting community development it was found that it was at a medium level with physical factors, environmental factors, economic factors, social factors respectively. 3. Guideline for Development Elder Persons Potentiality in Community Development Participation most elderly should have systematic thinking, experience, knowledge, and leadership thinking And have reasonably clear communication. Only use of knowledge, expertise to help develop the community. Developing the elderly from burdens to power. The participation of the elderly is to organize recreational activities for the elderly. Create a career to invite speakers. Teachers teaching careers that are suitable for the elderly. Management of the establishment of the club with the president of the club as a coordinator for participatory development and laying out a guideline for systematic and clear management.